تطور الدافعية الاكاديمية الذاتية لدى المراهقين من عمر( 13 – 15 ) سنة - عناد شيماء نصيف (lark, 2019)
Abstract This thesis aimed to identify the Academic Intrinsic Motivation , at ages (13, 14, 15) years, as well as, define discrepancy signs in the Academic Intrinsic Motivation according to the two variables(age and sex), for a research sample of (150) teenagers at a (50) teenagers for each age with equal samples for both sexes. The researcher depended the measure of Ubeiyis(2012) for the Academic Intrinsic Motivationwhich it was made for the fourth preparatory class students, in this research, the researcher had adjusted it for the students of intermediate stages. It’s consisting of (60) items. The researcher had verified the measure validity through: virtual validation. It had also been verified of scale reliability through: retest method. The researcher used many statistical tools for the analysis of information and processing it statistically, like: T-Test for one sample, analysis of dual disparity and the coefficient of Pearson correlation. The research had been clarified to the following results: • the Academic Intrinsic Motivationis built at (1315،14،) years age . • the Academic Intrinsic Motivationcan be considered as evolutional task in ages (13, 14, 15) years. • The development of the Academic Intrinsic Motivationis not affected by the sex variable. The researcher suggested many suggestions and recommendations.